Synthesis and Characterization of St-AN-(KH-570) Block Macromolecular Coupling Agent Copolymers - Cheng, Guojun; Song, Ruijuan; Miao, Jibing; Qian, Jiasheng (Asian Journal of Chemistry, 2013)
A new well-defined amphiphilic St-AN-(KH-570) block macromolecular coupling agent copolymers was successfully synthesized via free radical polymerization with styrene (St), acrylonitrile (AN) and g-methacryloxypropyl trimethoxy silane (KH-570) in dimethylbenzene. The compositions of copolymers were confirmed by Fourier transform infrared spectroscopy and proton nuclear magnetic resonance. Thermal analysis by differential scanning calorimetry indicated that glass transition temperature (Tg) of macromolecular coupling agent is much lower than polystyrene and polyacrylonitrile. The synthesis possessed the number average molecular weights (Mn) of 1.05 × 104 by gel permeation chromatography with broad polydispersity index value of 2.48.